Load-carrying capacity test of a long-span timber truss - Branco, J. (2016)
The aim of this work was to study the behaviour of existing timber trusses in order to improve the knowledge that may support engineers in the definition of more adequate restoration interventions in old buildings, particularly of long-span timber structures, as industrial or monumental constructions. For this purpose, a cyclic load-carrying test was carried out on a full-scale timber planar truss rescued from an old industrial roof structure. Before the tests, an accurate geometrical characterisation was performed and the biological condition of the timber elements was evaluated by non-destructive tests to determine their effective cross-section. The results of the destructive load-carrying test were used to calibrate a numerical model with the aim of assessing the effect of the effective crosssections of the truss components and the axial stiffness of the joints on the overall response observed during loading. The full-scale test performed proved the importance of this type of testing in assessing the behaviour of existing timber trusses. It is essential to assess the damage of the joints and to model correctly their behaviour so as to numerically reproduce the overall behaviour of timber trusses.